D.H. Lawrence correspondence, notes, and photographs - Lawrence, D. H. (David Herbert), 1885-1930.
Chiefly letters written by Lawrence to Mabel Dodge Luhan relating to his travels and experiences with Luhan in Taos, N.M., and to Lawrence's writing projects, including Lady Chatterley's Lover (1930). Also includes notes from Lawrence's wife, Frieda von Richthofen Lawrence; a letter from Havelock Ellis; and photographs.
British author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ellis, Havelock, -- 1859-1939 -- Correspondence; Lawrence, Frieda von Richthofen, -- 1879-1956 -- Correspondence; Luhan, Mabel Dodge, -- 1879-1962 -- Correspondence; New Mexico -- Description and travel; New Mexico -- Social life and customs; Taos (N.M.) -- Description and travel; Taos (N.M.) -- Social life and customs; Authors